1991
DOI: 10.1103/physrevc.44.390
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between energy and mass partition in the damped reactionHo165+

Abstract: Data from a kinematical coincidence experiment on the damped reaction ' Ho+' Ge at 8.5MeV/nucleon have been reanalyzed. Although the new analysis confirms the presence of some correlations between the excitation-energy division and the mass asymmetry, the magnitude of these correlations is found to be significantly smaller than that previously reported. Proton-neutron symmetry of the mechanism of heat generation through nucleon exchange is revealed and a possible acceptor-donor asymmetry of this mechanism is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The observed correlation between the total number of emitted nucleons and the net mass transfer indicates a non-equilibrium excitation energy partition between the reaction products, with an excess of excitation being deposited in the fragment which gains nucleons. Similar conclusions had been drawn by other authors [12][13][14][15][16], but remained quite controversial. Although the existence of such correlations is compatible, by itself, with a nucleon exchange picture, the fact that they are largely independent of the degree of inelasticity [11,15] is difficult to understand within the present versions of the stochastic nucleon exchange model and deserves new investigation.…”
supporting
confidence: 75%
“…The observed correlation between the total number of emitted nucleons and the net mass transfer indicates a non-equilibrium excitation energy partition between the reaction products, with an excess of excitation being deposited in the fragment which gains nucleons. Similar conclusions had been drawn by other authors [12][13][14][15][16], but remained quite controversial. Although the existence of such correlations is compatible, by itself, with a nucleon exchange picture, the fact that they are largely independent of the degree of inelasticity [11,15] is difficult to understand within the present versions of the stochastic nucleon exchange model and deserves new investigation.…”
supporting
confidence: 75%
“…However, with increasing dissipation, the larger and larger number of independent nucleon exchanges should almost wash out the correlation. Toke et al [10] emphasized the surprising constancy of the donor-acceptor intrinsic asymmetry η which they deduced from a re-analysis of the data of Ref. [4].…”
mentioning
confidence: 98%
“…The determination of the microscopic mechanism of energy dissipation and energy partition between the reaction partners of a dissipative collision has been a controversial subject of debate in the past years [1][2][3][4][5][6][7][8][9][10][11][12] (for a review see [13]). The excitation energy sharing presents an evolution with the inelasticity of the reaction: in quasi-elastic events the two reaction partners reseparate with almost equal excitation energies, but with increasing dissipation there is a trend towards equilibrium partition (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent reexamination [15][16][17] of some of the experimental data obtained in the kinematical coincidence experiments [6][7][8] at a few MeV per nucleon above the barrier has shown that the reported correlations result to a large extent from deficiencies in the data analysis procedure employed.…”
mentioning
confidence: 99%